UTILIZATION OF DIETARY LEVELS OF BAUCHI RED SORGHUM VARIETY BY STARTER BROILER CHICKENS - Doma, U. D.; Adamu, N. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
An experiment was conducted to evaluate the growth performance and financial benefits of starter broiler chickens fed dietary levels of Bauchi red sorghum variety. Five diets were formulated in which the red sorghum replaced maize at 0, 25, 50, 75 and 100% levels coded as diets A, B, C, D and E respectively. Two hundred broiler chickens were randomly allotted to five diets with 40 chicks per replicate in a completely randomized design (CRD). Feed and water were supplied ad libitum and the feeding trial lasted for a period of 28 days. The growth performance parameters revealed that starter weight (1147.50 -1167.50g), total weight gain (1030.50 – 1063.60g), daily weight gain (36.80 – 37.99g), total feed intake (2100.50 – 2130.50g), daily feed intake (75.01 – 77.81g), feed conversion ratio (1.98 – 2.10) and feed efficiency (0.46 – 0.50), were not significantly affected by the dietary levels of red sorghum variety. The survivability rate varied between 97.50 and 100% across the diets. Feed cost per kg gain decreased with increasing levels of red sorghum variety with a cost saving of 11.81% on diet E (100% RSV). Based on the results of this study, it was concluded that BRSV can completely replace maize as dietary energy source in starter broiler diets without compromising performance as well as reduction in feed cost.